Increasing emotional intelligence - Moriarty, Patricia (Trinity College (Dublin, Ireland). School of Psychology, 2008)
The aim of this thesis was to evaluate a programme to develop emotional intelligence in work teams. The thesis is presented in two studies. Study 1 describes the design, application and evaluation of a training programme and its effects on emotional intelligence in teams. The fundamental research question addressed was whether EI could be increased through training. Prior to answering this question, it became necessary to define emotional intelligence and select a model of emotional intelligence on which to base the design of the training intervention. Equally essential was the necessity to select an appropriate measure of EI that would reflect the complexity of EI within a workgroup. Study 2 investigated changes in the team process variables of communication, trust, decision making process quality, psychological safety and team development in participants over the same 12-week period.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin